Synthesis, Characterization And Anti-Mycobacterial Activity Of New 1,3,4-Oxadiazole Derivatives - Hasmaruddin, Nurul Syazana (2020)
A total of 20 new 2-alkylbenzysulfanyl-5-substituted-1,3,4-oxadiazoles derivatives (5a-j and 6a-j) were synthesized in four-step reaction pathways from carboxylic acid analogues as the starting materials, with moderate (40%) to excellent yields (92 %). These compounds continued a wide range of substituents including electron donating as well as electron-withdrawing groups. All these compounds were characterized using Fourier Transform Infrared (FT-IR) and Nuclear Magnetic Resonance (NMR) spectroscopy and elemental analysis. Some of the synthesized compounds were assayed for anti-mycobacterial activity against surrogate tuberculosis organisms (Mycobacterium smegmatis and Mycobacterium tuberculosis H3Ra). Fourteen compounds exhibited inhibition against M. smegmatis with MIC values in the range of 25-1600 μg/mL. Results of anti-mycobacterial assay against M. smegmatis showed that only 5c and 5d had good inhibition with MIC and MBC values of 78 μM and 68 μM, respectively. Some of the compounds showed moderate to weak inhibition. Interaction study of the respective compounds 5c and 5d with isoniazid against M. smegmatis using the checkerboard method produced an additive interaction. The time-kill assay on the combination of compounds 5c and 5d with INH against M. smegmatis produced a higher killing rate compared to drug INH at the end of the period of study which are 88.22 % and 77.10 %, respectively. Therefore, compounds 5c and 5d are potential anti-tuberculosis drug candidates.